THE EFFECT OF LEARNING STYLE AND VOCABULARY MASTERY TOWARD THE READING COMPREHENSION SKILL IN BEKASI - Mukhlasul Fasikh (Journal of English Language and Literature (JELL), 2018)
This study aims to check out the effect of learning style and vocabulary mastery toward the reading comprehension skill in the State of Junior High School in Bekasi. The method used in this research is expose facto with the correlation and regression analysis that is connecting between data showing the level learning style and vocabulary mastery toward the reading comprehension skill of students in the State of Junior High School in Bekasi. Sampling was done by random sampling technique. The respondents are 80 students in this research. The research instruments were the test questions with multiple choice forms and questionnaires. The results showed that: 1) there is a significant influence of learning style and vocabulary mastery interactively together toward the reading comprehension skill. This is evidenced by the acquisition of Sig value. 0,000 <0,05 and Fh = 16,150. Learning style and vocabulary mastery interactively contributed 29.6% toward the variable of reading comprehension skill. 2) There is a significant influence of the learning style toward the reading comprehension skill. This is evidenced by the acquisition of Sig value. 0.001 <0.05 and th = 3.295. Learning style variable contributed 15.72% in improving the reading comprehension skill. 3) There is a significant influence of vocabulary mastery toward the reading comprehension skill. This is evidenced by the acquisition of Sig value. 0.003 <0.05 and th = 3.019. Variable vocabulary mastery contributed 13.86% in improving the reading comprehension skill.